Epidemiology trend with particular spatio-temporal distribution of DIR in Malaysia - Jamil, Nur Izzah; Che Him, Norziha; Mohd Hamdan, Siti Fatimah Az-Zahra; Rusiman, Mohd Saifullah (2021)
Previous epidemiology record shows obvious trend of dengue fever that contribute to significant upsurge in the increasing number of dengue cases and deaths until the late nineteenth century with the sharp straight trend. This virus is transmitted to human by the bite of a female Aedes Aegypti mosquito, that could simply recognise by a white marking on its legs and lyre on the upper surface of its thorax. In Malaysia, dengue fever has been occurred since the first case in Penang around 1901 and continuously showed an intensity increment over the past few decades. The epidemics of dengue in Malaysia were observed predominantly confined to the densely populated and urbanised areas of Peninsular Malaysia (East of Malaysia) focusing in the Selangor state. Dengue cases that recorded in the nine district of Selangor state over seven years' period were used to ample evidence of dengue and peak transmission occurred in 2014, 2015 and 2019. The objective of this study was to access the dengue incidence rate according to the district in Selangor. The results were clustered by district based on the mean annual dengue incidence rate (DIR) values to classify the dengue risk categories. Among highest incidence rates were located at four districts; Petaling, Hulu Langat, Klang and Gombak where surrounding federal territory of Kuala Lumpur in the center of the region is on of main interest from high population densities and conclusion has been made that high DIR is strongly increase the risk of dengue incidence in that state.